Evaluation of the Effects of Vocational Home Economics Education on Graduates Career Choice in Edo State, Nigeria - Oshio, Lucy Ediruke (Journal of Pedagogy and Education Science, 2024)
Graduate unemployment and underemployment are major setbacks to socio-economic development as well as hindrances towards the attainment of the United Nations Sustainable Goal of zero poverty. In Nigeria, graduates unemployment and underemployment are compounding the complex problems of insecurity, drug abuse, and agitation for resource control. One way to address the above problem is to evaluate the influence university courses have on graduates’ future choice of careers. Hence the present study aimed to investigate the influence of the choice of technical education course on graduates’ future careers. A total of 200 graduates of the vocational Home Economics department from the University of Benin and Ambrose Alli University Ekpoma were surveyed. The majority of the respondents (27% -32%) reported that teaching aids during their undergraduate days boasted their interest in Vocational Home Economics. This was followed by another 21% to 34% who reported that family background was an encouraging factor. On the effects of Vocational Home Education on graduates future career choice, most of the surveyed graduates 31% - 34% agreed that their career after graduation was influenced by vocational home economics studied at the university, while 18% to 27% reported their knowledge of VHE did not influence their career choice after graduation. The study found that fashion stylists (18% - 20%), including tailoring and hairdressing, were the predominant occupations of graduates, followed by catering and restaurant owners (16% -17%). Of the surveyed graduates, over 50% agreed that they can meet their livelihood needs after graduation.